2003
DOI: 10.1029/2002jb002026
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric and asymmetric lithospheric extension: Relative effects of frictional‐plastic and viscous strain softening

Abstract: [1] Strain-dependent rheologies may play a critical role in the deformation of the lithosphere and particularly in the development of focused shear zones. We investigate the effects of strain softening on lithospheric extension using plane strain thermomechanical finite element model experiments. Parametric softening is specified as a linear decrease of the effective internal angle of friction, the effective viscosity, or both in the model rheologies. The sensitivity of deformation to the choice of softening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
293
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(304 citation statements)
references
References 39 publications
10
293
0
1
Order By: Relevance
“…Huismans and Beaumont (2013) predicted that during a rift stage distributed strain, and hence a wide rift basin, would progressively localise onto the rift axis. Although previous studies have demonstrated that this may happen during the continental rift phase (e.g.…”
Section: What Controls Fault Evolution From Continental Rift To Driftmentioning
confidence: 99%
“…Huismans and Beaumont (2013) predicted that during a rift stage distributed strain, and hence a wide rift basin, would progressively localise onto the rift axis. Although previous studies have demonstrated that this may happen during the continental rift phase (e.g.…”
Section: What Controls Fault Evolution From Continental Rift To Driftmentioning
confidence: 99%
“…Many numerical models include these features and have been used to study diverse aspects of rift dynamics in two dimensions (e.g. Zuber and Parmentier, 1986;Braun and Beaumont, 1989;Bassi, 1991;Buck, 1991;Burov and Cloetingh, 1997;Lavier et al, 2000;Behn et al, 2002;van Wijk and Cloetingh 2002;Huismans and Beaumont, 2003;Lavier and Manatschal, 2006;RegenauerLieb et al, 2006;Buiter et al 2008;Beaumont, 2011, Rey et al 2011 ). Despite these advantages, numerical models of oblique rifting intrinsically require computationally expensive calculations in three dimensions.…”
Section: B) Reconstruction Of the Margins At The Onset Of The Ocean-cmentioning
confidence: 99%
“…Strain weakening in the ductile middle crust permits mechanical decoupling between lower crustal flow and upper crust faulting, which is essential to promote localised faulting and large displacement along faults (Lavier and Buck, 2002;Huismans and Beaumont, 2003;Nagel and Buck, 2004;Schueller et al, 2005;Schueller et al, 2010). The absence of weakening in the deep crust yields to a progressive increase of its strength during strain localization so that it becomes the strongest level of the lithosphere, as is indicated by post-seismic creep measurements in California (Bürgmann and Dresen, 2008;Thatcher and Pollitz, 2008).…”
Section: / Discussion and Conclusionmentioning
confidence: 95%